2001
DOI: 10.1002/tox.1018
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of sodium selenate to two daphnids and three amphipods

Abstract: This study evaluated the acute toxicity of sodium selenate to two daphnid and three gammarid amphipod species. The daphnids, Ceriodaphnia dubia and Daphnia pulex, were evaluated in 48-hour static tests and the amphipods, Gammarus pseudolimnaeus, Gammarus lacustris, and Hyalella azteca, were evaluated in 96-hour static and flow-through tests. Tests resulted in mean LC50's of 1.92, 9.12, 1.82, 3.05, and 1.95 mg/L selenium for C. dubia, D. pulex, G. pseudolimnaeus, G. lacustris, and H. azteca, respectively. The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Some metals, including the AA standards of Al, Ge, Pb, and U, and the anion form of Cr, were much more toxic (Ͼ17-54-fold) in soft water. 24,2005 U. Borgmann et al Table 3. When this unusual observation was first made a Na X MO Y , Y ϭ 3 (Sb, Sn, Te) and 4 (all other salts); valence ϭ 4 (Sn, Te), 5 (Sb, V), 6 (Se, As, Cr, Mo, W), or 7 (Mn).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metals, including the AA standards of Al, Ge, Pb, and U, and the anion form of Cr, were much more toxic (Ͼ17-54-fold) in soft water. 24,2005 U. Borgmann et al Table 3. When this unusual observation was first made a Na X MO Y , Y ϭ 3 (Sb, Sn, Te) and 4 (all other salts); valence ϭ 4 (Sn, Te), 5 (Sb, V), 6 (Se, As, Cr, Mo, W), or 7 (Mn).…”
Section: Resultsmentioning
confidence: 99%
“…Chem. 24,2005 U. Borgmann et al Table 3 for LC50 estimate. could not be used because mortality curves for Hyalella tend to be fairly steep and a concentration series with each concentration increasing by a factor of 3.15 over the previous concentration usually will result only in one partial effect concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory effect of SeO 3 2− to the fungal growth of filamentous, polymorphic, and unicellular fungi has been demonstrated before (Gharieb et al 1995). Addition of , which is the least toxic Se oxyanion on an acute basis (Brix et al 2001;Canton 1999), caused a less inhibitory effect on the fungal growth. In agreement with the results of the present study, previous investigations showed that the addition of SeO 4 2− had less impact on the inhibition of the growth of other white-rot fungi, such as Bjerkandera adusta (Catal et al 2008), in comparison to SeO 3 2− .…”
Section: Inhibition Of Fungal Growth Induced By Selenium Oxyanionsmentioning
confidence: 94%
“…These two organisms are commonly used in the United States for testing waters and wastewaters (U.S. EPA, 1984). C. dubia is a sentinel invertebrate species widely used for toxicity testing in NPDES programs (Spehar and Fiandt, 1986, Mount et al, 1997Brix et al, 2001. P. promelas is a freshwater minnow that is also widely distributed in North America and is found in lentic systems.…”
Section: Task 3 Introductionmentioning
confidence: 99%